Igualdad y diferencia: dos niveles de análisis - Femenías, María Luisa (CUADERNOS KÓRE, 2012)
The aim of this paper is to explore the key concepts of feminism: equality and difference. This kind of exploration is essential in order to clarify the various spheres of meaning accompanying theoretical elaborations of the equality of individuals which, though supposedly merely formal, actually involve pre-Enligthtenment biases and are bound to establish both material and formal differences among subjects. Thus is revealed the need to rethink, through categories supplied by the Enlighthtenment but beyond the achievements of the Enlightenment itself, all those categorizations that result or exacerbate the actual exclusion of certain individuals (women, for instance) of the public space and which crystallize their unequal (in a meaning both material and formal) participation in it. But it is equally necessary to rethink the difference itself and to shed light on the recent identitarian speechs.